Environment, vegetation and greenness (NDVI) along the North America and Eurasia Arctic transects - Walker, D. A.; Epstein, H. E.; Raynolds, M. K.; Kuss, P.; Kopecký, M. (Martin); Frost, G. V.; Daniëls, F. J. A.; Leibman, M. O.; Moskalenko, N. G.; Matyshak, G. V.; Khitun, O. V.; Khomutov, A. V.; et al. (Anthropocenes – Human, Inhuman, Posthuman, 2012)
In this paper, we describe environment, species composition, biomass and spectral properties of vegetation plots established along two long (> 1500 km) transect spanning all bioclimate subzones of North America and Eurasia Arctic. Despite considerable differences in environment and species composition between the transects, there is a close relationship between spectral properties and biomass along both transects. This relationship can be used for biomass modeling across the whole arctic and provide important insights into climate change impact on this unique ecosystem.